A Comparison of the Origin of Idioms in Mandarin and Indonesian - Huang Haiyan; I Dewa Putu Wijana; Tatang Hariri (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
In language, idioms can function as stand-alone semantic units because they contain whole concepts. These concepts, formed from human thought, can be explored to discover cultural elements which served as the basis for idiom creation. If the origins of an idiom are known or recognized, that idiom’s meaning can be understood more easily. Idioms are frequently used by language communities in their day-to-day lives. However, the origins of idioms in the Indonesian language has almost never been discussed or researched. This article compares the origins of idioms in Mandarin and in Indonesian. It finds that the origins of idioms in Mandarin and in Indonesian are diverse, but in general fit one of two main types: they may be adapted from foreign languages (most importantly in idioms related to religion), or be created within the society and reproduced from generation to generation. Idioms can be traced to either the written tradition or the oral tradition. Idioms in Mandarin generally originate from the written tradition, whereas idioms in Indonesian tend to originate from orality. This study uses the theory of meaning formation first proposed by Ogden and Richards (1911). The comparative method of data analysis is used here, as the origins of idioms in Mandarin and Indonesian are compared.